Pengaruh Manajemen Modal Kerja Terhadap Penjualan - Supriadi, Yoyon (STIE Kesatuan, 2010)
This research was done to find out the influence of working capital on companyâs sales circulation, by conducting case study at PT Gudang Garam Tbk. and PT Hanjaya Mandala Sampoerna Tbk. Working capital is one of very important factors to run daily operational activity of the company. It more or less can be meant as working capital management. The result of this research proves that working capital and sales circulation have significant correlation, where F-statistics value 43,825 and F-table 5,538 constitute significance as high as 0,07 at PT Gudang Garam Tbk. The correlation between working capital and sales circulation is -0,967. It means the variables have negative correlation, which shows that when the working capital increases, the sales circulatian will decrease. And on the contrary, when the working capital decreases, the sales circulation will increase.